Identification of Precise Therapeutic Targets and Characteristic Prognostic Genes Based on Immune Gene Characteristics in Uveal Melanoma - Zhang, Zhenxi; Su, Jingyu; Li, Li; Du, Wenjing (Frontiers in Cell and Developmental Biology, 2021)
The tumor microenvironment is an important factor for the immunotherapy of tumor patients. The sequenced transcriptome data can be used to describe the tumor microenvironment and various immune subtypes. We exploited published data on patients with uveal melanoma (UVM) to identify immune subtypes. Based on the immune-related gene sets of 80 patients with UVM in the TCGA database, we used consensus clustering to identify two immune subgroups. In the two immune subtypes, we analyzed clinical characteristics and immune infiltration. Class1 has low immune infiltration, contains memory B cells, Th2 cells, Th17 cells, eosinophils, natural killer cells, and has a better prognosis. Class2 has higher immune infiltration. CD8+ T cells, Th1 cells, MDSCs, and Dendritic cells are enriched in class2, which has strong cytolytic activity, high expression of immune checkpoint genes, and poor outcome. Moreover, we have developed and verified an immune characteristic model that can predict the prognosis of patients well. Through this model, we screened prostaglandin-endoperoxide synthase 2 (PTGS2) as the therapeutic target of UVM. Treatment of choroidal melanoma cell line (OCM1) cells with celecoxib (an inhibitor of PTGS2) effectively inhibits cell growth, proliferation, and promotes apoptosis. Our results show the immunological heterogeneity of UVM patients and also provide an ideal therapeutic target for the future treatment design of patients.